Ethnomycolgical Knowledge on Uses of Wild Mushrooms in Western and Central Nepal - Adhikari, M.K.; Devkota, S.; Tiwari, R.D. (Our Nature, 2006)
This paper highlights the knowledge on the uses of various wild mushrooms by the different ethnic castes and community inhabiting in the vicinities of Lumle (Kaski, western Nepal) and Kathmandu valley (central Nepal). The research carried out revealed that among 24 species 18 mushrooms are used as culinary, 8 for medicinal value and 3 for other purposes. Key Words: Clavariales, Ethnomycology, Kathmandu, Lumle, Mushrooms, Nepal doi:10.3126/on.v3i1.329 Our Nature (2005)3: 13-19